Physiological and Performance Impacts After Field Supramaximal High-Intensity Interval Training With Different Work-Recovery Duration - Brandão, Leandro Henrique Albuquerque; Chagas, Thaysa Passos Nery; Vasconcelos, Alan Bruno Silva; de Oliveira, Vivian Conceição; Fortes, Leonardo de Sousa; de Almeida, Marcos Bezerra; Mendes Netto, Raquel Simões; Del-Vecchio, Fabrício Boscolo; Neto, Ezequias Pereira; Chaves, Leury Max Silva; Jimenez-Pavón, David; Da Silva-Grigoletto, Marzo Edir (Frontiers in Physiology, 2020)
High-intensity interval training (HIIT) has numerous external load control variables. The management of these variables makes the physiological responses and performance presented by athletes also modify. The present study aimed to assess the activity of CK and LDH enzymes, performance and metabolic responses caused by two HIIT protocols above the maximum in male recreational runners. Fifteen recreational male runners performed two HIIT protocols in randomized order with multiple conditions: 1) H15 (n = 15), with a HIIT protocol of 15:15 work-recovery duration, and 2) H30 (n = 15) with a HIIT protocol of 30:30 work-recovery duration. Both protocols were performed at similar intensity (130% vV̇O2max), one set until voluntary exhaustion. Blood samples were collected and used to capture the levels and activities of blood lactate (BLac: mmol⋅L–1), glucose (GLU: mg⋅dL–1), creatine kinase (CK: U⋅L–1), and lactate dehydrogenase (LDH: U⋅L–1). BLac and GLU were collected at pre, five, and ten minutes after the H15 and H30 protocols were performed. Blood samples were used to measure the activities of CK and LDH enzymes, which were verified 24 h before and 48 h after the protocols. The distance traveled (m), total time (s), and bouts performed (rep) were also registered. Significant differences between conditions H15 and H30 were observed in the bouts performed (p = 0.001; ES = 1.19). Several statistical differences were found over time for BLac [pre vs. post 5 (both conditions: p = 0.001), pre vs. post 10 (both conditions: p = 0.001), and post 5 vs. post 10 (H30: p = 0.004)], CK [pre vs. post 24 (H15: p < 0.001; ES = 0.97 and H30: p = 0.001; ES = 0.74) post 24 vs. post 48 (H30: p = 0.03; ES = 0.56)], and LDH [pre vs. post24 (H15: p = 0.008; ES = 1.07 and H30: p = 0.022; ES = 0.85). No statistical differences between conditions were observed for any blood parameter. Thus, the volunteers exhibited equal performance in both protocols, which resulted in a similar physiological response. Despite this similarity, in comparison to H15, the H30 protocol presented lower CK activity post 48 and lactate levels after 10 min post protocol.